UJI EFEKTIVITAS EKSTRAK ETANOL DAUN SAMBUNG NYAWA (Gynura procumbens) SEBAGAI ANTIHIPERGLIKEMIA PADA MENCIT (Mus musculus) YANG DIINDUKSI GLUKOSA - Yuliana Dewi; Christianto Adhy Nugroho; Leo Eladisa Ganjari (Program Studi Biologi - Universitas Katolik Widya Mandala Surabaya (kampus Kota Madiun), 2023)
Hyperglycemia is a disease characterized by a continuous increase in blood glucose levels and if left unchecked can cause diabetes mellitus (DM). Continuing life leaves are one of the medicinal plants that are believed to reduce blood glucose levels. The purpose of this study was to determine the ability of ethanol extract of continuing life leaves (Gynura procumbens) in lowering blood glucose levels. This experimental design uses an experimental method with a form of pretest-posttest control group design research. A total of 16 mice were divided into 4 groups randomly, namely the negative control group given Na CMC 0.5%, positive control given glibenclamide dose 0.65 mg/kg BB, group III ethanol extract of continuing life leaves dose 150 mg/kg BB, group IV ethanol extract of continuing life leaves dose 200 mg/kg BB. Glucose administration is given 30 minutes after treatment. Observations were made at minutes 0, 60, and 120. The results of this study showed that continuing life leaf extract can reduce mouse blood glucose levels and the effective dose is 200 mg/ kg BB